2017
DOI: 10.1002/2017jb014294
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Rupture Modeling of the M7.2 2010 El Mayor‐Cucapah Earthquake: Comparison With a Geodetic Model

Abstract: The 2010 Mw 7.2 El Mayor‐Cucapah earthquake is the largest event recorded in the broader Southern California‐Baja California region in the last 18 years. Here we try to analyze primary features of this type of event by using dynamic rupture simulations based on a multifault interface and later compare our results with space geodetic models. Our results show that starting from homogeneous prestress conditions, slip heterogeneity can be achieved as a result of variable dip angle along strike and the modulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
4
10
0
Order By: Relevance
“…Similar to Fialko et al (2010), Wei, Fielding, et al (2011), Wei, Sandwell, et al (2011), Kyriakopoulos et al (2017), and Huang et al (2017), most of the slip is found near the epicenter (Pescadores Fault) and at the end of the Indiviso fault. However, in the preferred model of Kyriakopoulos et al (2017), the slip from the Pescadores Fault to the Borrego Fault does not show any interruption while we are able, instead, to find a good correspondence with areas having low or no slip like the PIAZ and PAZ accommodation zones (Figures 1 and 12). Our joint inversions also show a greater and deeper slip at the southernmost plane, with respect to the starting solution of Huang17.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar to Fialko et al (2010), Wei, Fielding, et al (2011), Wei, Sandwell, et al (2011), Kyriakopoulos et al (2017), and Huang et al (2017), most of the slip is found near the epicenter (Pescadores Fault) and at the end of the Indiviso fault. However, in the preferred model of Kyriakopoulos et al (2017), the slip from the Pescadores Fault to the Borrego Fault does not show any interruption while we are able, instead, to find a good correspondence with areas having low or no slip like the PIAZ and PAZ accommodation zones (Figures 1 and 12). Our joint inversions also show a greater and deeper slip at the southernmost plane, with respect to the starting solution of Huang17.…”
Section: Discussionsupporting
confidence: 81%
“…However, in the preferred model of Kyriakopoulos et al. (2017), the slip from the Pescadores Fault to the Borrego Fault does not show any interruption while we are able, instead, to find a good correspondence with areas having low or no slip like the PIAZ and PAZ accommodation zones (Figures 1 and 12). Our joint inversions also show a greater and deeper slip at the southernmost plane, with respect to the starting solution of Huang17.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…The fault ruptured northward to southernmost California just across the California/Mexico border (Figure ). Two main fault segments connected by a smaller extensional fault ruptured away from the epicenter with dominantly right‐lateral strike‐slip motion (J. M. Fletcher et al, ; Huang et al, ; Kyriakopoulos et al, ; Wei et al, ) and with an additional smaller segment striking slightly more northerly terminating the north end of the rupture. The segments dip northwest south of the epicenter and northeast north of the epicenter.…”
Section: Introductionmentioning
confidence: 99%
“…An initial elastic dislocation model by Fialko et al () indicates 59° and 89°SW dips along the southern and northern Indiviso fault, a 79°NE dip on the Laguna Salada fault, and 71°NE dips on three segments that approximate the Pescadores, Borrego, and Paso Superior faults (Figure d). This model has since been used as the basis for dynamic rupture simulations (Kyriakopoulos et al, ) and modeling of postseismic deformation (González‐Ortega et al, ). An alternative model by Wei et al () shows a 60°SW dip on the Indiviso fault, a 60°NE dip for a fault segment approximating the Laguna Salada, Pescadores, and Borrego faults, and a 50°NE dip for the Paso Superior fault (Figure e).…”
Section: Overview Of the El Mayor‐cucapah Earthquakementioning
confidence: 99%